2011
DOI: 10.1007/s10900-011-9465-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome: Factors Affecting Time to Arrival in a Diverse Urban Setting

Abstract: This study seeks to better understand how individuals of different cultural/ethnic backgrounds in an urban setting assess the signs and symptoms of Acute Coronary Syndrome (ACS) and the ensuing decision to take urgent action. Few studies exist which examine these differences and enhance understanding of how to address these differences and, ultimately, reduce morbidity and mortality from ACS. Face-to-face interviews were conducted with a convenience sample of urban patients of different cultural and socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Our findings were also similar to Deshmukh et al 16 who examined a sample of four ethnic minority groups in New York and found that Haitians, Caribbeans, African Americans and Hispanics all delayed significantly longer than the recommended 3 hours for reperfusion therapy. However, after adjusting for multiple factors known to increase prehospital delay, including race, age, sex, diabetes, diagnosis, number of symptoms, symptom distress, and abrupt vs. gradual symptom onset, race was not a significant predictor in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings were also similar to Deshmukh et al 16 who examined a sample of four ethnic minority groups in New York and found that Haitians, Caribbeans, African Americans and Hispanics all delayed significantly longer than the recommended 3 hours for reperfusion therapy. However, after adjusting for multiple factors known to increase prehospital delay, including race, age, sex, diabetes, diagnosis, number of symptoms, symptom distress, and abrupt vs. gradual symptom onset, race was not a significant predictor in our study.…”
Section: Discussionsupporting
confidence: 90%
“…6 Despite well-known reductions in morbidity and mortality when patients receive treatment within three hours of symptom onset, 13,16,17 Blacks experiencing ACS symptoms have longer pre-hospital delay times compared to Whites. 18-20 Additional prehospital delay by Blacks may be a result of limited healthcare access, variations in symptoms, lack of understanding of the significance of symptoms, 6 or socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous studies investigating presentation, diagnosis, and management of acute coronary syndrome (ACS) and the influence of race [1, 9••, 4648]. Despite the attention, recent studies continue to demonstrate disparities in management and outcomes.…”
Section: Acute Coronary Syndromementioning
confidence: 99%
“…Furthermore, there is an influence on how individual patients of different cultural backgrounds respond to chest pain, for example to symptoms of the acute coronary syndrome. [ 19 ] These assumptions are supported by the fact that the Swiss Thoracic Pain in Community (TOPIC) study, which was performed in a time period and with a population comparable to those in the German SESAM 2 study, revealed a nearly equal consultation frequency of chest pain [ Table 4 ]. However, the higher rate in the German SESAM 2 study is unlikely to be influenced by attention bias since the study estimated total morbidity.…”
Section: Discussionmentioning
confidence: 99%